Evaluation of Senior High School History’s Program Curriculum Implementation of Curriculum 2013 in the Province of DKI Jakarta - Sumardiansyah Perdana Kusuma; Diana Nomida Musnir; Zulfiati Syahrial (International Journal of Business, Economics, and Social Development, 2021)
The purpose in this study to evaluate of Senior High School (SMA) Historys Program Curriculum Implementation in Jakarta Province. This study used the CIPPO program evaluation model includes: (1) Context, consisting of the fundamental framework, curriculum standards, and curriculum goals; (2), Input, consisting of elements of curriculum developers, principal, teacher, and student; (3) Process, consisting of planning, learning, and assessments; (4) Product, and the effect of history (5) Outcomes, consisting of history.This research is qualitative with documentation studies, interviews, and observations, which are then enriched with a quantitative data in the form of tests. Data analysis techniques include data collection, data condensation, data presentation, and conclusions. The population studied were SMAN 70, SMAN 48, SMAN 77, and SMAN 18 which implemented Curriculum 2013 and opened a class Science Social Knowledge (IPS) where the subjects of History Indonesia and History Interest in the same academic Interest in Students. The results of the study show that there is a systemic bias, starting from stakeholder understanding, curriculum documents, processes by teachers, learning outcomes, to learning outcomes in the implementation of the High School History Curriculum in the 2013 Curriculum in DKI Jakarta Province.